Prosecutorial Regulation Versus Prosecutorial Accountability - Bibas, Stephanos (2009)
No government official has as much unreviewable power or discretion as the prosecutor. Few regulations bind or even guide prosecutorial discretion, and fewer still work well. Most commentators favor more external regulation by legislatures, judges, or bar authorities. Neither across-the-board legislation nor ex post review of individual cases has proven to be effective, however. Drawing on management literature, this article reframes the issue as a principal-agent problem and suggests corporate strategies for better serving the relevant stakeholders. Fear of voters could better check prosecutors, as could victim participation in individual cases. Scholars have largely neglected the most promising avenue of reform, namely changing the internal structure and management of prosecutors' offices. Leaders could do more to develop office cultures, norms, and ideals that value more than just maximizing conviction statistics. Hierarchical office structures and internal procedural and substantive office policies could promote deliberation, give fair notice, and increase consistency. Hiring, training, promotion, and tenure practices could better shape prosecutors and their behavior. Pay structures and feedback from judges, defense counsel, and victims could encourage good behavior. Finally, publishing more data on charges, convictions, plea bargains, and sentences could also improve accountability